PENGGUNAAN MANGA HUMOR DALAM PEMBELAJARAN BAHASA DAN PENELITIAN BAHASA JEPANG (THE USE OF HUMOR MANGA IN JAPANESE LANGUAGE LEARNING AND RESEARCH) - Akhmad Saifudin (Jurnal Japanedu: Pendidikan dan Pengajaran Bahasa Jepang, 2017)
The purpose of this study is to explore various ways and benefits of using the manga humor in Japanese language learning and research. The manga used in this study is comic strip manga humor. The study was conducted by giving the task to the students to read and observe one manga story. The students were asked to explain the characters of manga and to explain the language phenomena contained in the manga story. The results of the observations on the manga were then discussed in the classroom to determine what language phenomena can be learned from the manga and how to learn them. The results of this study found that in the manga humor there are many interesting things that can be learned. Manga can also be used as effective learning media and to generate interest and motivation of learners, both in Japanese learning and Japanese language research. In terms of language learning, manga humor can be an interactive medium that can improve the four language skills and in learning Japanese language research, manga humor play an important role in bringing the idea and provide an overview of how research on Japanese language is done by looking at the linguistic phenomena that exist in the manga.